Kinetics of proteolysis of hog gastric mucin by human neutrophil elastase and by Pseudomonas aeruginosa elastase. - Poncz, L (1988)
Human neutrophil and Pseudomonas aeruginosa elastases were compared for their ability to degrade hog gastric mucin, which was used as a model substrate. P. aeruginosa elastase was more active than neutrophil elastase, and 2 to 10 peptide bonds were hydrolyzed within 5 min. The results demonstrate that both elastases degrade mucins actively at concentrations comparable to physiological levels of neutrophil elastase, which raises the possibility that proteolysis of mucins may be one mechanism of damage during chronic infection and inflammation of the respiratory tract.